The Effect of Hybrid Nano Addition on the Color Stability of Maxillofacial Rehabilitation Silicone Material after Weathering - Shahad Fadhil Bunyan; Fatanah Mohamad Suhaimi; Faraedon Mohidden Mostafa Zardawi; Siti Noor Fazliah Mohd Noor; Muhammad Azrul Zabidi (Medical Journal of Babylon)
Background: Facial prostheses may get discolored and change color from intrinsic and extrinsic coloring due to external factors. This is related to the inherent color stability of elastomers and colorants. Objectives: We aimed to evaluate the effect of hybrid nano additives on the color stability of Tech-Sil25 room-temperature vulcanized silicones used for maxillofacial prosthesis after artificial weathering. Materials and Methods: A total of 70 samples were fabricated for fourteen groups. Seven groups contained 0.2 wt% burnt sienna, and another seven groups contained 0.2 wt% cobalt blue. The seven groups were the control groups. Each group consists of five samples. The samples were exposed to artificial weathering for 300 h. The CIELAB color system was used to record the color values. It aids in the numerical classification of color differences by describing the three color coordinates (or color values) x, y, and z in three unique corresponding values of L, a, and b, respectively. Results: Burnt sienna pigment samples with hybrid nano 1%NS+1%NA show the highest color stability, followed by 2% NS and 2% NA; the least color change was observed (ΔE* about = 1.1) by the visual system as the threshold was seen. The cobalt blue pigment shows the most significant color change. The color shift observed in all groups was within the clinically acceptable level. Conclusion: It can be concluded that a 2% hybrid nano additive can improve the color stability for both pigment groups (burnt sienna and cobalt blue). The variation in color in the burnt sienna group was less than that in the cobalt blue groups. The color change in each group came within an acceptable range for clinical purposes.